A dyadic analysis of social network stability before and after incarceration. (September 2022) - Sentse, Miranda; de Vries, Ieke; Nieuwbeerta, Paul
Abstract: Purpose: To examine tie stability from pre- to post imprisonment among incarcerated people focusing on 1) ties with core discussion and criminal network members, 2) ties measured before and after imprisonment, and 3) dyadic (tie)-level determinants while accounting for important individual characteristics. Methods: Our sample comprises 1180 network ties of 464 incarcerated males in the Netherlands participating in the Prison Project, interviewed three weeks upon entering prison and six months after release. Multilevel logistic regressions were used to examine which relationship characteristics (quantity, quality, and type) and individual characteristics impact tie stability. Results: Relationship quantity (contact frequency), quality (trust, support), and type (family, partner) contribute to tie stability post-imprisonment. Having ties with criminal or delinquent alters did not affect tie stability. Moreover, after accounting for these tie-level variables, characteristics of the respondent (e.g., sentence length, agreeableness, employment) were not significant predictors of tie stability. Conclusions: A tie level perspective adds new information to social network changes surrounding a period of imprisonment. Investing in factors (e.g., contact frequency) contributing to tie stability during imprisonment may facilitate reintegration policies, which should accommodate - through awareness and training - relationships that remain stable post-imprisonment and foster social support to facilitate successful reentry. Highlights: A tie level perspective adds new information to network changes after imprisonment. Tie quantity, quality, and type contribute to tie stability post imprisonment. Criminality of alter does not affect tie stability. Future research should investigate why these characteristics affect tie stability.